AI Tools for Academic Writing: Insights from Indonesian Graduate Students - Nur Muthmainnah; Faizal Risdianto; Ahmad Bukhori Muslim; Anastasya Ludfie Ayu Sholichah; Ema Widia Ningrum Ayu (Faculty of Education and Teacher Training of UIN Palopo, 2026)
This study aims to identify which AI tools Indonesian graduate students use for academic writing and how aware they are of AI's use in their writing. A survey was administered to 79 graduate students to collect data for this study. The results indicate that ChatGPT is the most frequently utilized AI model, alongside various others that help improve students’ English writing and comprehension skills. The participants also demonstrated an understanding of the necessity of engaging with AI-generated writing for their academic needs and acknowledged the importance of maintaining research ethics when employing these tools. In summary, students are effectively using AI chatbots, especially ChatGPT, to support their academic writing. Their significant awareness of AI's role suggests they recognize that human contribution is still crucial in the writing process. The results of this study provide valuable insights into the AI tools that enhance academic writing among graduate students in Indonesia. It also presents the level of graduate students’ awareness of the position of AI tools in academic writing. Thus, it is advisable to reassess research ethics regarding the extent to which generative AI models can be incorporated into academic writing. Given its educational implications, universities should develop guidelines for the ethical and appropriate use of AI and clarify AI support limitations within their educational frameworks.